MYL5 as a Novel Prognostic Marker is Associated with Immune Infiltrating in Breast Cancer: A Preliminary Study - Minghe Lv (Hindawi-Wiley, 2023)
Background. Myosin light chain plays a vital regulatory function in a large-scale cellular physiological procedure, however, the role of myosin light chain 5 (MYL5) in breast cancer has not been reported. In this study, we aimed to elucidate the effects of MYL5 on clinical prognosis and immune cell infiltration, and further explore the potential mechanism in breast cancer patients. Methods. In this study, we first explored the expression pattern and prognostic value of MYL5 in breast cancer across multiple databases, including Oncomine, TCGA, GTEx, GEPIA2, PrognoScan, and Kaplan-Meier Plotter. The correlations of MYL5 expression with immune cell infiltration and associational gene markers in breast cancer were analyzed by using the TIMER, TIMER2.0, and TISIDB databases. The enrichment and prognosis analysis of MYL5-related genes were implemented by using LinkOmics datasets. Results. We found that there was a low expression of MYL5 in breast cancer than in corresponding normal tissue by analyzing the data from Oncomine and TCGA datasets. Furthermore, research showed the prognosis of the MYL5 high-expression group was better than the low-expression group in breast cancer patients. Furthermore, MYL5 expression is markedly related to the tumor-infiltrating immune cells (TIICs), including cancer-associated fibroblast, B cell, CD8+ T cell, CD4+ T cell, macrophage, neutrophil, and dendritic cell, and related to immune molecules as well as the associated gene markers of TIICs. Conclusion. MYL5 can serve as a prognostic signature in breast cancer and is associated with immune infiltration. This study first offers a relatively comprehensive understanding of the oncogenic roles of MYL5 for breast cancer.